Chromatin Conformation of Integrated Moloney Leukemia Virus DNA Sequences in Tissues of BALB/Mo Mice and in Virus-Infected Cell Lines - Breindl, Michael (1980)
The technique of preferential DNase I digestion of transcriptionally active chromatin regions was used to study the structural organization of integrated Moloney murine leukemia virus (M-MuLV) proviral sequences in various cells carrying integrated viral genomes. BALB/Mo mice, which carry M-MuLV as an endogenous virus at a single Mendelian locus, were used to examine the genetically transmitted viral genome copy and additional M-MuLV sequences acquired somatically during leukemogenesis. It has been shown previously that M-MuLV genome expression in these mice is restricted to lymphatic target tissues. In young homozygous BALB/Mo mice carrying one M-MuLV genome copy per haploid mouse genome in all cells we found that the genetically transmitted viral genome copy was in a preferentially DNase I-sensitive conformation in lymphatic target tissues, whereas in nontarget tissues the same sequence was not preferentially DNase I sensitive. This suggests that the chromatin conformation and the transcriptional activity of the integrated proviral genome are related to and probably determined by the state of cellular differentiation. In target tissues from BALB/Mo mice examined at different ages and in different stages of leukemogenesis the majority of the new somatically acquired M-MuLV sequences were preferentially DNase I digestible. A very similar pattern of DNase I digestibility was observed in target tissues from BALB/c mice exogenously infected with M-MuLV. This shows that in these tissues somatically acquired proviral sequences integrate preferentially or exclusively at sites of the host genome in which they are in a transcriptionally active chromatin conformation. Alternatively, the chromatin structure of the respective host genome region may be changed after the integration of viral DNA. In nontarget tissues from BALB/Mo mice the M-MuLV-specific sequences remained DNase I resistant throughout the lives of the animals. A different pattern of DNase I digestibility was observed in virus-infected cell lines which had been produced by low-multiplicity infection, cloned, and selected for virus production. When cell lines harboring different numbers of M-MuLV proviral copies were examined, it was found that a minority of the proviral sequences (on the average only one M-MuLV genome copy per haploid mouse genome) were preferentially digestible by DNase I, independent of the total number of proviral genome copies present. This suggests that the chromatin conformation of newly acquired proviral sequences is influenced by the state of differentiation of the infected cell or the way infected cells are selected or both.